Implementation of Suction Technique for Airway Cleaning Is Not Effective in Stroke Patients at Vita Insani Pematangsiantar Hospital - Pakpahan, Jarina (CV. Devitara, 2024)
Stroke is a disturbance in the function of the nervous system caused by a disturbance in blood circulation in the brain due to rupture of blood vessels or due to blockage of blood vessels in the brain. One of the nursing problems that arises in cases of hemorrhagic stroke is ineffective airway clearance. Efforts made to overcome airway clearance are the use of suction techniques. This research design is quantitative-descriptive using a case study approach. The research sample consisted of 2 respondents, namely hemorrhagic stroke sufferers. The sampling used in this research was purposive sampling. Data was collected using observation techniques, interviews, physical examination, supporting examinations, documentation carried out on May 22 2024 and June 21 2024 at Vita Insani Pematangsiantar Hospital. The results of this study show that after implementing suction for 3 days, it was found that both patients experienced a decrease in respiratory frequency, in patient 1 the first day from 22 x/minute to 20 x/minute, patient 2 respiratory frequency 23 x/minute to 21 x/minute minutes and mucus can be expelled, vesicular breath sounds, regular breathing rhythm and sonor lung percussion in both patients. Suction technique can improve airway clearance in haemorrhagic stroke patients, Researchers recommend that nurses be able to implement suction techniques in hemorrhagic stroke patients to overcome the problem of ineffective airway clearance.